Aboveground carbon storage in a freshwater swamp forest ecosystem in the Niger Delta. Issue 3 (3rd July 2016) - Igu, Nwabueze I.; Marchant, Rob
ABSTRACT: Tropical forests are important stores of carbon but the contribution of freshwater swamp forests to this store is largely unquantified. This study provides detail on the aboveground carbon (AGC) store of freshwater swamp forests and the transition zones into mangrove forests in the Niger Delta. We present taxonomic data of tree stems ≥ 10 cm diameter at breast height (DBH) from 24 1-ha plots established across different disturbance gradients and transition zone and terrestrial forest. The AGC ranged widely around a mean value of 228 t/ha (bootstrapped 95% confidence interval (CI) 168, 288) in intact forests, to 104 t/ha (bootstrapped 95% CI: 64, 144) in disturbed freshwater forests and 100 t/ha (bootstrapped 95% CI: 60, 141) in forests transitional into mangrove characterized by decreased disturbance. Our study suggests that the variations in AGC of West African swamp forests are mainly a function of the differences in stand structure and stem sizes of the trees in each forest that relate largely to historical use and current management of the forest resources. Conserving disturbed forests alongside other intact forests will help to increase not only the carbon budget of the region but also its diverse biodiversity and other ecosystem services.